Solving global nutrition and dietary challenges: More than proteins - Brouwer, Inge D.; Talsma, Elise (VU University Press, 2023)
The global focus on protein transition must not detract attention from other nutritional and dietary challenges that are at least as important, specifically the high prevalence of vitamin and mineral deficiencies in low-and middle-income countries. Unlike in many high-income countries, low- and middle-income countries may benefit from increased access to and consumption of animal-sourced foods. Policymakers should set locally tailored dietary guidelines and look beyond proteins to the food system as a whole.